ANALISIS PENGGUNAAN DEEP TRANSLATOR ALAT UNTUK PENERJEMAHAN TEKS BAHASA ARAB - Ainur Rahma; Ismi Khairani; Desi Susanti (Lembaga Pengembangan Kinerja Dosen, 2025)
This research analyzes the use of Deep Translator in the translation of Arabic texts, focusing on the accuracy, contextual relevance and effectiveness of this tool compared to human translators. This research uses a descriptive qualitative method, which involves analyzing the results of Deep Translator's translations of religious and academic texts and comparing them with manual translations. The data is also supported by a literature review that has relevance to the topic of this research. The results show that Deep Translator excels in its speed and ability to translate texts with simple structures, such as news or everyday texts. However, it faces significant limitations in understanding cultural context, idiomatic meanings, and nuances of complex texts, especially in religious texts such as Qur'anic verses and muthola'ah. Deep Translator produces literal translations that reflect less historical and cultural meaning than human translators. This shortcoming is also evident in muthola'ah texts, where Deep Translator's diction choices are less relevant for certain readers.